The influence of Jules Lagneau’s philosophical ideas on the formation of Alain’s educational views (Emile-Auguste Chartier) - Мартьянова, Марія Євгеніївна; Martianova, Maria Evgeniivna (Vienna: “East West” Association for advanced studies and higher education GmbH, 2017)
Abstract: The article underlines the role of the Jules Lagneau’s philosophic principles in the Alain’s educative conception. The article presents the analyze of the ethics direction of Alain’s research and procedure development in the context of the study of the education. Анотація: У статті окреслена роль філософських принципів французького викладача Жуля Ланьо у концепції викладання його учня Алена (Еміля Огюста-Шартьє). Проаналізовано витоки етичного спрямування науково‑методичної діяльності Алена в контексті розгляду питань процесу виховання.
Вплив філософських ідей Ж. Ланьо на формування педагогічних поглядів Алена (Еміля-Огюста Шартьє)
Keywords: freedom of the mind; perception; free will; moral concept; judgment; свобода розуму; сприйняття; вільна воля; етична концепція; судження